Konstruksi Prinsip Syariah dalam Investasi Dana dan Tabungan Haji - Agustina, Vina; Anwar, Khairul (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This study aims to describe the implementation of sharia values in the concept of Hajj fund and savings investment. This study uses a qualitative method in the form of a literature review. Data sources were taken from scientific literature relevant to the subject matter. Data collection techniques were conducted through documentation techniques. Meanwhile, data analysis techniques were conducted using qualitative descriptive analysis techniques. The research findings conclude that Hajj fund management must adhere to Sharia principles, which include security, prudence, and value for money. This is important to ensure that investments not only provide financial benefits but also fulfil the social and religious objectives of Hajj fund management. This study contributes to the importance of the paradigmatic awareness of Muslims, that investment funds and hajj savings not only function as financial instruments but also as a means to achieve maslahah (goodness) for Muslims in Indonesia.